Long‐term outcome of a combined surgical approach for repair of femoral avulsion fracture of the caudal cruciate ligament in a dog. Issue 2 (14th June 2020) - Bourbos, Alexandros; Cinti, Filippo; Baroni, Massimo; Piola, Valentina; Pisani, Guido
Abstract : A four‐month‐old male boxer dog was presented with a one‐week history of acute right hindlimb lameness after an injury. Physical and radiographic examinations confirmed a femoral avulsion fracture of the caudal cruciate ligament. Surgical repair was elected using a combination of arthroscopy and arthrotomy to place a monofilament absorbable suture material through the parallel bone tunnels to reduce the avulsed bone fragment. The last follow‐up examination 2.5 years postoperatively showed good to excellent limb function and mild periarticular changes.